2008
DOI: 10.3132/pcrj.2008.00024
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tiotropium bromide and combined ipratropium/salbutamol for the treatment of COPD: a UK General Practice Research Database 12-month follow-up study

Abstract: Tiotropium is associated with a reduced risk of exacerbations and COPD-related referrals and hospitalisation compared to combined ipratropium/salbutamol in patients with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
1
17
0
1
Order By: Relevance
“…Findings from randomised controlled trials are complemented by results from a recent casecontrol study supporting efficacy of tiotropium in a real-life setting. 23 Our analysis, which accommodates all available long-term data with tiotropium 18mcg once daily to date and which provides level 1A evidence on tiotropium efficacy, 24- . 27 This trial showed that tiotropium was associated with a 14% reduction in COPD exacerbations and associated hospitalisations.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from randomised controlled trials are complemented by results from a recent casecontrol study supporting efficacy of tiotropium in a real-life setting. 23 Our analysis, which accommodates all available long-term data with tiotropium 18mcg once daily to date and which provides level 1A evidence on tiotropium efficacy, 24- . 27 This trial showed that tiotropium was associated with a 14% reduction in COPD exacerbations and associated hospitalisations.…”
Section: Discussionmentioning
confidence: 99%
“…These generally use information from administrative or prescribing databases and have the strength that they include all types of patients (age, sex, smoking status, FEV 1, co-morbidities). 21 Yet interpretation of these studies can be difficult; the outcomes observed may be confounded by the fact that clinicians obviously had a reason to prescribe the therapy and thus there are likely to be systematic differences between patients who received the intervention and those who did not. 22 Although attempts are often made to try to control for these confounders, some of the information upon which the decision was made may not be available in the database and many proponents of evidence-based medicine dismiss observational studies: "If you find that [a] study was not randomised, we'd suggest that you stop reading it and go on to the next article."…”
Section: Are the Results Applicable In Patients Of All Types?mentioning
confidence: 99%
“…Actually, there is documentation from a retrospective study, which used real-life data, that tiotropium is associated with significantly better disease outcomes in all measures investigated when compared to salbutamol/ ipratropium [46]. Unfortunately, there is no data yet available on the benefit of LABA/LAMA FDC over LAMA, and also LABA, in real life although the results of pivotal randomized clinical trials indicate that this is the case.…”
Section: Lama/laba In the Prevention Of Exacerbationsmentioning
confidence: 99%